European Psychiatric/Mental Health Nursing in the 21st Century A Person-Centred Evidence-Based Approach (Principles of Specialty Nursing, Under the auspices of the European Specialist Nurses Organisations (ESNO),, 2018)
This groundbreaking book has a number of features that set it apart from other textbooks on this subject: Firstly, it focuses on interpersonal, humanistic and ecological views and approaches to P/MH nursing. Secondly, it highlights patient/client-centered approaches and mental-health-service user involvement. Lastly, it is a genuinely European P/MH nursing textbook - the first of its kind - largely written by mental health scholars from Europe, although it also includes contributions from North America and Australia/New Zealand. Focusing on clinical/practical issues, theory and empirical findings, it adopts an evidence-based or evidence-informed approach. Each contribution presents the state-of-the-art of P/MH nursing in Europe so that it can be transferred to and implemented by P/MH nurses and the broader mental health care community around the globe. As such, it will be the first genuinely 21st century European Psychiatric Mental Health Nursing book.